(untitled) (Applied Biological Research, 2023)
Various drugs are available to combat Candida infections by targeting sterol 14α-demethylase (CYP51) enzyme involved in ergosterol biosynthesis. However, most drugs have limitations due to the adversities and development of drug resistance by Candida species. Our study aimed at exploring natural alternatives in combating Candida-based infections for which antifungal efficacy of some selected antioxidants was evaluated using computational biology tools. The herbal molecules rosmarinic acid (RA), methyl rosmarinic acid (MRA), α tocopherol (AT) and α-tocopherol acetate (ATA) were used as ligands for docking with CYP51 of C. albicans and C. glabrata using PatchDock docking tool. The drug likeliness analysis was done using Lipinski filter and AdmetSAR. The binding efficiency of RA, MRA, AT, ATA and fluconazole for CYP51 of C. albicans were observed to be -302.25, -346.74, -393.33, -442.80 and -280.21, respectively, while for CYP51 ofC. glabrata it was-309.89, -324.47, -428.24,-464.5 and -256.6, respectively. All the selected molecules showed better binding affinity to CYP51 in both Candida species with respect to fluconazole, and also satisfied the criteria of drug likeliness. The present study demonstrated the potent drug likeliness of the four molecules that may contribute in designing novel in vivo therapeutic strategies against Candida infections.